Jurnal Pendidikan: the correlation between vocabulary mastery and grammar: asace study toward the first year students of english department of STKIP YDB L.A - Yosa novia dewi, Zefriyenni (Makmal pendidikan, 2017)
vocabulary mastery is one of imporant aspect in grammar ability